Kinerja Hidrolika Sistem Fertigasi Mikro - Naswir .; Soedodo Hardjoamidjojo; Nora H. Pandjaitan; Hidayat Pawitan (Jurnal Keteknikan Pertanian, 2008)
A micro fertigation system was designed using local components, simple and easy to build, operate and repair by farmers. Evaluation of hydraulic performances consists oflong-path size in emitters, relationship between discharge and head in emitter, head loss along the lateral, and emission uniformity. The result of the research indicated that the micro fertigation system with 0,5 mm inside diameter micro-tubing used to control the flow from outlets along laterals. The individual microtube was 0,6 m long and spaced at 0,3 m interval along laterals. The discharge was adjusted by stop valves and ranges from 0,48 -2, 74 ltrs/h at operating heads of 0,2-1,5 m. The emission exponent, x was 0,86, and the head-discharge equation was Qe= 1,94 H0,86. The coefficient of manufacturing variation, CV was 0,043 from 125 samples of emitters, and an interpretation of values was excellent. Accordingly allowable length of lateral (at operation head, H = 1 m) 15 meters of length PVC hose ¼ inch size was acceptable and 25 meters of length PVC hose 5/16 inch size was acceptable. The design of micro fertigation system have emission uniformity, EU > 85% far all treatments.  Keywords: micro fertigatian system, hydraulic performance, emission exponent, head loss, emission uniformity Diterima: 6 Agustus 2007; Disetujui: 12 Nopember 2007